2019
DOI: 10.2174/1574888x13666180913123424
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Trials of Mesenchymal Stem Cell Therapy in Skin Diseases: An Update and Concise Review

Abstract: Skin is one of the crucial body organs which its anatomy and physiology are linked with various disorders including congenital or acquired diseases. Nowadays, mesenchymal stem cell (MSCs)-based therapy has become a promising therapeutic field, which is expected to help in the treatment of the most costly and incurable diseases. However, it could be questioned whether the use of MSCs has improved in clinical trials studies and diseases treatment. In this study, we review the clinical trials using MSCs in skin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 99 publications
0
100
0
Order By: Relevance
“…Among these, MSCs has attracted attention due to source potential, a high proliferation rate, low invasive procedure, and free of ethical issues. There is much superiority in using MSC therapy in comparison with other treatments [23], including in I) They are easily accessible and can be isolated from various tissues such as bone marrow and adipose tissues, including in umbilical cord, dental pulp, menstrual-blood, buccal fat pad, fetal liver, etc. ; II) They are multipotent stem cells; III) MSCs can easily expand to clinical volume in a suitable period of time; IV) MSCs can be stored for repetitive therapeutic usage; V) Clinical trials of MSCs so far haven't shown adverse reactions to allogeneic MSC; VI) Safety and effectiveness of MSCs have been obviously documented in several clinical trials [23].…”
Section: Mesenchymal Stem Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, MSCs has attracted attention due to source potential, a high proliferation rate, low invasive procedure, and free of ethical issues. There is much superiority in using MSC therapy in comparison with other treatments [23], including in I) They are easily accessible and can be isolated from various tissues such as bone marrow and adipose tissues, including in umbilical cord, dental pulp, menstrual-blood, buccal fat pad, fetal liver, etc. ; II) They are multipotent stem cells; III) MSCs can easily expand to clinical volume in a suitable period of time; IV) MSCs can be stored for repetitive therapeutic usage; V) Clinical trials of MSCs so far haven't shown adverse reactions to allogeneic MSC; VI) Safety and effectiveness of MSCs have been obviously documented in several clinical trials [23].…”
Section: Mesenchymal Stem Cell Therapymentioning
confidence: 99%
“…Recently, China, USA, Jordon, Iran, and several other countries have begun cell-based therapy clinical studies and some reports have been published (Table 1). Interestingly, one of the available methods to evaluate its efficacy in the maintenance or repair of damaged vital organs is the use of mesenchymal stem cell (MSCs) therapy that widely used in the treatment of type 2 diabetes, autoimmune disease, spinal cord injury, GVHD and several other diseases specially with high immunity rates have been used [23,[26][27][28]. MSCs, using their immunomodulatory properties and their differentiation ability, can prevent lung tissue death by counteracting the cytokine storm and regeneration and reconstruction of damaged tissues (Fig.…”
Section: Msc Clinical Trials For Covid-19mentioning
confidence: 99%
“…Hence, Cur synergistically exhibited good recuperation in combination with stem cell therapy in some diseases such as hepatocellular carcinoma and severe spinal cord injury . Currently, therapies based on mesenchymal stem cells (MSCs) are one of the crucial pieces of RG medicine subcategories that has become a hopeful therapeutic approach in which anticipated becomes contributory in the skin disease's treatment with different types such as Epidermolysis Bullosa (EB), Atopic dermatitis, cutaneous burns and diabetic foot ulcers . MSCs can be harvested from different tissues such as bone marrow, fat, skin and so on .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, therapies based on mesenchymal stem cells (MSCs) are one of the crucial pieces of RG medicine subcategories that has become a hopeful therapeutic approach in which anticipated becomes contributory in the skin disease's treatment with different types such as Epidermolysis Bullosa (EB), Atopic dermatitis, cutaneous burns and diabetic foot ulcers . MSCs can be harvested from different tissues such as bone marrow, fat, skin and so on . Adipose tissues hold great promise in cell and tissue‐based therapy as they are a low invasive source and are available in large quantities as waste material .…”
Section: Introductionmentioning
confidence: 99%
“…As another part of the tissue engineered construct, several stem cells can be used to differentiate into IPCs. Mesenchymal stem cells (MSCs) are one of the cells used today to treat a variety of diseases at the clinic and clinical trial levels (Golchin, Farahany, Khojasteh, Soleimanifar, & Ardeshirylajimi, 2019;Steinert, Rackwitz, Gilbert, Nöth, & Tuan, 2012). Depending on the type and location of the diseases, these cells can be prepared from various adult tissues.…”
mentioning
confidence: 99%